Análise experimental e avaliação das incertezas em medição de líquidos com referência tipo ball prover - Lavezzo, Luís Fernando de Queiroz (2010)
This work is dedicated to the reference measurement of liquid flow aiming to deal with the peculiarities related to the subject, which reach great importance in commercial transactions involving typical interests of the oil industry. The flow measurement process however is not deterministic and involves a large number of variables that contributes to the doubt about of the real value that it proposes to measure. Such variables, which contribute to uncertainty in measurement, include a lot of aspects such constructive feature meter, fluid properties, environmental conditions and operator ability, for instance. This work presents a prototype project of a laboratorial scale ball prover, experimentally evaluate its performance, aiming to point out its alignment with the requirements established by the norms, considering the uncertainties in the measurement and the contribution of different lengths. Otherwise, it is procedured a comparison with a turbine meter calibrated by the manufacturer.